Peculiarities of the microscopic description of multipole excitations : Doubly-open shell spherical nuclei - Egido, J. L. (1978)
The microscopic description of the first 2+ and 3− levels of spherical nuclei (90≦A≦150 and 186≦A≦206) is examined, both in the Tamm-Dancoff and the Random Phase Approximations. Peculiar effects of the schematic model are discussed. The consistency of the theory is investigated.